Pengaruh ROE Dan CR Terhadap Return Saham Indeks LQ45 - Sari, Andini Kartika; Elizabeth, Sri Megawati (MDP Student Conference, 2024)
This study was conducted to determine the effect of ROE and CR on stock returns in LQ45 Index companies. The scope of this study is to discuss how the influence of ROE and CR on the return of shares of companies listed on the LQ45 Index. The research method used in this study is quantitative method. The type of data used is secondary data. The sample in this study amounted to 15 companies using the purposive sampling method. Data testing using the help of SPSS application version 21. The results show that ROE and CR have an influence on Stock Return